Analisis Penerapan Algoritma C4.5 Dalam Mengukur Tingkat Kepuasan Pelanggan Indihome Pada Kota Pematangsiantar - Yovan Bastian; Heru Satria Tambunan; Widodo Saputra (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
The purpose of this study was to study the level of customer satisfaction with Indihome services in Pematangsiantar City by using the C4.5 Algorithm. The source of the data used in the study is to conduct observations and interviews by distributing questionnaires to Indihome customers in Pematangsiantar City. The results of this study are expected to be able to determine Indihome customer satisfaction so that service levels are in accordance with the provisions of the indicator.